Subtlety of Ambient-Language Effects in Babbling: A Study of English- and Chinese-Learning Infants at 8, 10, and 12 Months. Issue 1 (2nd January 2017) - Lee, Chia-Cheng; Jhang, Yuna; Chen, Li-mei; Relyea, George; Oller, D. Kimbrough
ABSTRACT: Prior research on ambient-language effects in babbling has often suggested infants produce language-specific phonological features within the first year. These results have been questioned in research failing to find such effects and challenging the positive findings on methodological grounds. We studied English- and Chinese-learning infants at 8, 10, and 12 months and found listeners could not detect ambient-language effects in the vast majority of infant utterances, but only in items deemed to be words or to contain canonical syllables that may have made them sound like words with language-specific shapes. Thus, the present research suggests the earliest ambient-language effects may be found in emerging lexical items or in utterances influenced by language-specific features of lexical items. Even the ambient-language effects for infant canonical syllables and words were very small compared with ambient-language effects for meaningless but phonotactically well-formed syllable sequences spoken by adult native speakers of English and Chinese.